Application of Sidra 4.0 Software Traffic Flow in Intersection in Kuala Lumpur - B. Z. Alshetwi, Abduraouf.; Atiq Abdullah O.K. Rahmat, Riza; Nazri Borhan, Muhamad; Ismael Albrka Ali, Shaban; Imhimmed Mohamed Irtema, Hamza (International Journal of Engineering and Technology, 2018)
Traffic signals are one of the most effective Traffic Flow and flexible active traffic control utilized extensively in a number of global cities. The traffic signal benefits include an organized traffic movement, an increased intersection capacity and needs only modest geometric design. Furthermore, there are numerous significant methods in improving network performance by directing the traffic lights’ flow at the intersection. This study showed, together with the capability of improving the level of service (LOS), the intersection light signal volume, fuel consumption (FUC), average delay (AVD), operating costs (OPC), Carbon dioxide emissions (CO2E) and travel speed (TS). The Jalan Kampung Pandan intersection light signal capacity is 1985.3, Jalan Imbi – Raja Chulan 1793.2 and Jalan Imbi 3238.1. The FUC present condition is approximately 58,881.3 lit/s from Jalan Raja Imbi- Chulan, in addition to 34,687.6 lit/s Jalan Kampung Pandan on the trip, along with 55,173.6 lit/s to Jalan Imbi railway journey. Additionally, the results displays that the quantity of OPC acquired was 1138847.2 RM/hr for Jalan Raja Imbi- Chulan, 659235.5 RM/hr for Jalan Kampung Pandan and 1054115.7 RM/hr for Jalan Imbi. The CO2E results amount of CO2E attained were 147203.3 to Jalan Raja Imbi- Chulan, in addition to 86719.1 Jalan Kampung Pandan and 137934. To Jalan Imbi. Peak Travel speed at TS intersection current status is approximately 0.5 km/h from Jalan Imbi- Raja Chulan, along with 0.8 km/h for Jalan Kampung Pandan in the trip, together with 1.2 km/h to Jalan Imbi on a trip.